Anthropological Knowledge as Universal: A Critical Analysis of Fahrenheit 451. - Ullah, Ubaid; Bukhari, Syeda Muqaddas Hameed (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
The current research is a critical study of Bradbury's